Account of the recent discovery of the Remains of David’s Tower at Edinburgh Castle - Oldrieve, W T (Proceedings of the Society of Antiquaries of Scotland, 1914)
The construction of David's Tower began in 1367 and took more than ten years to complete. Excavation revealed the lower entrance to the ground floor of the putative tower. The doorway was medieval in character and a number of masons' marks were revealed in the stonework. The structure was filled with loose soil and debris. Artefacts included cannonballs, burst iron shells, coins of Edward I or II, glass wine flagons, clay pipes, pottery vessels and a soldier's iron helmet. The nearby well, first documented in 1313 was also examined. The results of the excavation are combined with documentary and cartographic evidence to suggest that the structure is indeed David's Tower.